Epidemiology of injuries in Australian school level rugby union. Issue 8 (August 2017) - Leung, Felix T.; Franettovich Smith, Melinda M.; Brown, Mark; Rahmann, Ann; Mendis, M. Dilani; Hides, Julie A.
Abstract: Objectives: There is a high incidence of injuries in rugby union due to the physical nature of the game. There is a lack of large-scale injury surveillance data reported for school level rugby players of different ages. Our study aimed to investigate the frequency and nature of injuries being sustained during an Australian school level rugby union season. Design: Prospective observational study. Methods: Injury surveillance was conducted on 3585 rugby players from all 8 schools participating in an interschool rugby competition in Queensland, Australia. Match injury data were collected using paper-based injury recording forms during the season using a 'medical-attention' injury definition for each age group from opens (17 and 18 year olds) through to year 5 teams (9–10 year olds). Results: There were 332 injuries recorded over 14, 029 player hours during the season. The overall rate of injury was 23.7/1000 player hours (95% CI, 21.2–26.3). The incidence of upper and lower limb injuries were 6.3 and 5.6 injuries/1000 player hours respectively (95% CI, 5.1–7.8 and 4.5–7.0). The incidence of suspected concussion injuries was 4.3/1000 player hours (95% CI, 3.6–5.5). Injuries differed across age groups and tackling was the most common mechanism of injury. Conclusions: The injury patterns observed in this large sample of players could be used to guide injury prevention programs in school level rugby union. Injury prevention programs should include age appropriate interventions and focus on improving the techniques used during the contact phase of rugby.